2017
DOI: 10.1159/000477962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Infliximab Therapy in Children with Crohn's Disease Using Trough Levels Predictors

Abstract: Background: In adults, infliximab (IFX) levels correlate with disease activity, and antibodies to IFX (ATIs) predict treatment failure. We aimed to determine the association of IFX levels and ATIs with disease activity in a paediatric population. We prospectively collected blood, stool, and clinical data from 65 patients (age 10.5-15.1 years) with Crohn's disease (CD) before IFX administration, and measured IFX trough levels, ATIs, and faecal calprotectin levels (CPT). Samples were collected during maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…In multivariate analysis, our data showed YP tended to develop ATIs more frequently than OP. In line with other studies in PIBD [3,6,13,14,24], a positive association between IFX trough levels and shorter interval length was found. As expected, within our cohort of PIBD patients, ATI positivity was associated with lower IFX trough levels.…”
Section: Discussionsupporting
confidence: 92%
“…In multivariate analysis, our data showed YP tended to develop ATIs more frequently than OP. In line with other studies in PIBD [3,6,13,14,24], a positive association between IFX trough levels and shorter interval length was found. As expected, within our cohort of PIBD patients, ATI positivity was associated with lower IFX trough levels.…”
Section: Discussionsupporting
confidence: 92%
“…Faecal calprotectin, blood parameters such as C‐reactive protein and albumin, and, in particular, trough serum anti‐TNF levels are the most relevant 7,8 . Thus, the paediatric population has proven to be similar to the adult population in terms of the inverse correlation between serum infliximab trough levels and disease activity, as measured in terms of C‐reactive protein and faecal calprotectin 9–11 . The same association between trough serum infliximab levels and response was observed for adalimumab 12 .…”
Section: Introductionmentioning
confidence: 80%
“…However, no association was found between Alb level and the serum IFX level in this study, and Alb was not included as one of the candidate hematological parameters. Ohem et al 32. showed that higher CRP and ESR levels were found in pediatric patients with lower IFX TLs.…”
Section: Discussionmentioning
confidence: 98%
“…Median serum IFX levels of 17.6 μg/mL during interventional treatment and 3.55 μg/mL during maintenance therapy were determined from a study of pediatric patients 35. In a model that used CRP level <0.5 mg/dL as the definition of laboratory remission, the optimal IFX TL was 3.5 μg/mL 32. In this study, serum IFX level of 9.82 μg/mL was required to maintain a CRP level at below 0.5 mg/dL in induction therapy.…”
Section: Discussionmentioning
confidence: 99%